2020
DOI: 10.1016/j.jbef.2020.100404
|View full text |Cite
|
Sign up to set email alerts
|

A time–frequency analysis of the impact of the Covid-19 induced panic on the volatility of currency and cryptocurrency markets

Abstract: We apply wavelet analyses to examine the impact of the Covid-19 fueled panic on the volatility of major fiat and cryptocurrency markets during January-May, 2020. There is high coherence between moves of the Coronavirus Panic Index and the price moves in Euro, British pound, and Renminbi currencies as well as movements of the Bloomberg Galaxy Crypto Index. The main conclusions for each index pair are quite similar and corroborate with our thesis that the cross-currency hedge strategies, which could work under n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
115
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(122 citation statements)
references
References 34 publications
6
115
0
1
Order By: Relevance
“…A careful scrutiny of the literature suggests that COVID-19 effects have been investigated on several close, yet distinct financial market variables. These studies focus on equity markets ( Al-Awadhi et al, 2020 ; Goodell, 2020 ; Li et al, 2020 ; Pavlyshenko, 2020 ; Sharif et al, 2020 ; Topcu and Gulal, 2020 ), commodities such as oil and gold, and alternative assets, such as cryptocurrencies ( Bakas and Triantafyllou, 2020 ; Corbet et al, 2020; Umar et al, 2020 , Umar and Gubareva, 2020 ), the debt market ( Arellano et al, 2020 ; Qiang et al, 2020 ; Sène et al, 2020 ) and mutual funds ( Mirza et al, 2020 ; Yarovaya et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A careful scrutiny of the literature suggests that COVID-19 effects have been investigated on several close, yet distinct financial market variables. These studies focus on equity markets ( Al-Awadhi et al, 2020 ; Goodell, 2020 ; Li et al, 2020 ; Pavlyshenko, 2020 ; Sharif et al, 2020 ; Topcu and Gulal, 2020 ), commodities such as oil and gold, and alternative assets, such as cryptocurrencies ( Bakas and Triantafyllou, 2020 ; Corbet et al, 2020; Umar et al, 2020 , Umar and Gubareva, 2020 ), the debt market ( Arellano et al, 2020 ; Qiang et al, 2020 ; Sène et al, 2020 ) and mutual funds ( Mirza et al, 2020 ; Yarovaya et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, the literature on the spillover, safehaven, cross-market interdependence, and hedging opportunities across assets and financial markets has attracted lot of attention since the subprime crisis of 2007 (Gubareva and Borges 2016;Umar and Suleman 2017;Riaz, Shehzad, and Umar 2019;Stereńczak, Zaremba, and Umar 2020;Kenourgios, Umar, and Lemonidi 2020;Umar and Gubareva 2020). The recent Covid-19 pandemic has presented a unique challenge and inspired a new stream of literature focused on the impact of this pandemic on financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies conducted indicate that the cryptocurrency market in the pandemic periods showed a safe haven feature in shortterm shocks [17][18][19][20]. Umar and Guberava [21] examined the interaction between the Ravenpack panic index and Euro, British Pound and Renminbi currencies, Galaxy Crypto Index in the Covid 19 period with wavelet analysis. They stated that cross-currency hedging strategies used in the normal period are likely to fail in a crisis like the Covid 19.…”
Section: Literature Reviewmentioning
confidence: 99%